Deep veins thrombosis in children with blood diseases - P. A. Zharkov; D. S. Morozova; D. A. Gobadze; D. A. Evstratov; D. V. Fedorova; L. I. Zharikova; A. V. Pshonkin; G. A. Novichkova (Онкогематология, 2019)
Background. Children and adolescents undergoing treatment in the hospital for blood diseases are at risk of thrombotic complications. However, to date no major studies of the prevalence of thrombosis in this category of patients have been conducted in Russia. The objective: to determine the incidence of symptomatic and asymptomatic deep vein thrombosis (DVT), as well as their distribution by gender and age in children with various blood disorders. Materials and methods. Medical records of 1962 patients, aged from 0 to 17 years, were retrospectively analyzed. All DVT cases were confirmed by visualization methods. The presence of thrombosis clinical signs detected during physical examination, allowed identifying symptomatic DVT. Results. DVT was diagnosed in 429 patients; the symptomatic (n = 110) and asymptomatic (n = 337) DVT were considered as two independent groups with cases of thrombosis. The highest incidence of thrombotic complications was found in children with acute lymphoblastic leukemia (ALL) – 30.77 %, non-Hodgkin’s lymphomas – 22.58 %, other malignant blood disorders – 18.75 %, myeloid leukemia – 15.63 %, Hodgkin’s lymphoma – 16.50 %, histiocytosis – 12.5 %, aplastic anemia – 7.94 %, other leukemia – 7.14 %. Symptomatic episodes were more common in patients with lymphomas, especially non-Hodgkin’s, and ALL, while asymptomatic DVT were more common among children with ALL. Conclusion. The DVT prevalence in children with blood disorders exceeds 20 %, most of them are asymptomatic thrombosis, while symptomatic DVT are much less common. Patients receiving treatment for lymphomas and ALL have the highest number of venous thrombotic complications. Further research is needed to address the need for primary thrombotic prophylaxis in children with blood disorders.